Distribution of cytochrome P450*4 (CYP2A6*4) allele gene among Javanese Indonesian T2DM patients - Christine Patramurti; Dita Maria Virginia (Pharmaciana, 2021)
Smoking had been increasing the risk factor of type 2 diabetes mellitus (T2DM), both active and passive smokers, which is caused by nicotine contained in cigarettes. Nicotine has metabolized by cytochrome p450 2a6 (CYP2A6) enzyme coded by the CYP2A6 gene. This gene was a high polymorphism that is the CYP2A6*4 allele gene was inactive. Thus, our objective was to describe the CYP2A6*4 allele gene among active and passive Javanese smokers with T2DM. From this cross-sectional study, we identified this allele gene among 46 of the adults with T2DM, which were consist of 23 active smokers and 23 passive smokers. The CYP2A6*4 allele gene identification has done using polymerase chain reaction (PCR) methods. The CYP2A6*4 allele frequency was analyzed to describe the distribution of this allele among the participants. This study supports the hypothesis that smoking, including cigarette smoke, was an environmentally modifiable risk factor for developing T2DM. Based on our result, the allele frequency among the participants was 42.39%. A high frequency of the CYP2A4 allele gene among the participants was indicating that the CYP2A4 allele gene was also the other risk factor in developing T2DM.